Fifteen minute consultation: When can I use a medical app?. Issue 5 (18th September 2020) - Rowe-Setz, Gala; Behringer, Wilhelm; Roland, Damian; Lyttle, Mark D; Jahn, Haiko Kurt
Abstract : Advances in mobile device technology and internet connectivity have created powerful new mobile health (mHealth) and telemedicine capabilities. The guidelines regarding mHealth use in the clinical environment can be conflicting, which has resulted in some reluctance by institutions and medical staff to fully embrace these advances due to privacy and patient confidentiality concerns among others. The COVID-19 response has led to departments to reconfigurate care and revisit mHealth as a tool to allow social distancing and remote care. This article reviews mHealth guidance in practice and describes its use and interpretation as rapid decision-making aid and in telehealth.